“How Should One Live?” The “Lives” of Henry James and Martha C. Nussbaum’s Conception of Moral Philosophy (American & British Studies Annual, 2014)
The 21st century has witnessed an unprecedented novelistic attention on Henry James and, consequently, multiple resurrections of the Master in the form of James-based or James-influenced works of fiction. Some of the questions bothering novelists, critics and readers alike have been: How to portray James, his life and genius, when there are as many variants of James as there are critics and biographers writing about him? How to write about a life when the life itself, a hypotext, is veiled in ambiguity and uncertainty? In what way should the gaps be filled or what explanations ought to be provided? Should one follow the Master or rebel against him? The present paper wishes to discuss how Martha C. Nussbaum’s theoretical underpinnings of moral philosophy might prove helpful in performing a critical and comparative reading of the “lives” of Henry James. The Master by Colm Tóibín and Author, Author by David Lodge will be subjected to qualitative analysis within the interpretative framework provided by Nussbaum’s theory postulated in Love’s Knowledge, which applies moral philosophy to the discussion of literary works.
Keywords: Henry James; Martha C. Nussbaum; moral philosophy; biographical novel